Utilization of Uncaria gambir Roxb leaf extract as a reducing agent in the green synthesis of Ag/TiO2 composites and its application for multifunctional towels. Issue 11 (June 2023) - Sahadewo, Adam Haikal; Elysabeth, Tiur; Slamet,
Unhygienic use of towels can cause bacterial infections. Therefore, it is necessary to develop anti-bacterial, self-cleaning, hydrophilic towels. TiO2 photocatalyst modification with Ag nanoparticles can add these properties to towels. However, the problem is the process of reducing Ag ions, which usually uses chemical reducing agents that are dangerous, toxic, and expensive. This study aims to utilize gambir leaf extract as an alternative reducing agent so that Ag/TiO2 synthesis can be carried out using a green process. The results of field emission scanning electron microscopy characterization showed that the use of gambier leaf extract as a reducing agent did not cause aggregation or agglomeration. Ultraviolet-visible diffuse reflectance spectroscopy analysis showed that the bandgap energy of Ag/TiO2 prepared using gambir leaf extract as the reducing agent was only slightly higher than that of its counterpart. Fourier transform infrared spectroscopy characterization showed an increase in the number of OH groups on the Ag/TiO2 towels compared to the blank towels. This proves that Ag/TiO2 towels have superior hydrophilic properties. The results of the anti-bacterial, self-cleaning, and hydrophilic tests showed that the optimal Ag loading in various tests was 3%, which could disinfect up to 33% of the bacteria and possessed the best self-cleaning, absorption capacity, and drying rates.